Femininity and Masculinity across the Menstrual Cycle : A relation to Mate Value - Hromatko, Ivana; Tadinac, Meri; Vranić, Andrea (2008)
Numerous studies have shown that menstrual cycle related variations in sex hormones influence various cognitive processes. These shifts are considered as the evidence for a hormone-mediated adaptive design underlying human mating motivation. In a series of related studies we have shown that (i) femininity does not vary across the menstrual cycle, whereas masculinity is the most pronounced during the fertile period, (ii) masculinity, but not femininity, predicts shifts in spatial cognition across the menstrual cycle, and (iii) women with different positions on masculinity and femininity dimensions differ in their self-perceived mate value. These results suggest that (i) there might be a hormone mediated psychological mechanism making a woman more assertive and dominant during a short time-window when the conception is likely, (ii) menstrual cycle related shifts in cognitive abilities and mating motivation might have a common hormonal mechanism, and (iii) women’ s mate value (and indirectly her reproductive success) depends upon both feminine and masculine traits.
Projekt MZOS
Projekt MZOS
ENG